Membrane Design Criteria and Practical Viability of Pressure-Driven Distillation - Liu, Weifan; Wang, Ruoyu; Straub, Anthony P.; Lin, Shihong (Environmental science & technology, 2023)
Pressure-driven distillation (PD) is a novel desalination technology based on hydraulic pressure driving force and vapor transport across a hydrophobic porous membrane. In theory, PD offers near-perfect rejection for nonvolatile solutes, chlorine resistance, and the ability to decouple water and solute transport. Despite its advantages, pore wetting and the development of a reverse transmembrane temperature difference are potential critical concerns in PD, with the former compromising the salt rejection and the latter reducing or even eliminating the driving force for vapor transport. We herein present an analysis to evaluate the practical viability and membrane design principles of PD with a focus on the dependence of flux and salt rejection (SR) on membrane properties. By modeling the mass transfer in a PD process under different conditions, we arrive at two important conclusions. First, a practically detrimental reverse transmembrane temperature difference does not develop in PD under all relevant circumstances and is thus not a practical concern. Second, for a PD process to achieve an acceptable SR, the membrane pores should be at the nanometer scale with a highly uniform pore size distribution. This analysis demonstrates the practical viability of PD and provides the principles for designing robust and high-performance PD membranes.